2006
DOI: 10.1038/sj.ki.5000160
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathologic characteristics of focal segmental glomerulosclerosis pathologic variants

Abstract: Histologic variants of idiopathic focal segmental glomerulosclerosis (FSGS) may have prognostic value. A recent working classification system has distinguished five FSGS variants. We evaluated a cohort of adult patients with biopsy-proven FSGS diagnosed between March 1982 and July 2001 to determine if subtypes were associated with renal outcome. Renal biopsies were reviewed by two pathologists. Demographic and clinical data were obtained from charts. Outcomes were partial and complete remission of the nephroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
200
4
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(225 citation statements)
references
References 22 publications
16
200
4
5
Order By: Relevance
“…This study identified NOS as the most common subtype, comprising 68% of this cohort, followed by collapsing (12%), tip (10%), perihilar (7%), and cellular variants (3%) (4,5). In comparison, FSGS subtyping at Columbia University showed 62.3% NOS or perihilar variants, 23.7% collapsing, 9.4% tip, and 4.5% cellular variants (4).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This study identified NOS as the most common subtype, comprising 68% of this cohort, followed by collapsing (12%), tip (10%), perihilar (7%), and cellular variants (3%) (4,5). In comparison, FSGS subtyping at Columbia University showed 62.3% NOS or perihilar variants, 23.7% collapsing, 9.4% tip, and 4.5% cellular variants (4).…”
Section: Discussionmentioning
confidence: 80%
“…The FSGS-CT findings support significant differences in demographic features between histologic subtypes. Tip and collapsing variants were more common in teenagers and adults than children (5,6,12,(14)(15)(16)(17)(18)(19). Only 29% of tip patients were children aged 2-12 years at onset of FSGS, whereas 43% were over 18 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter might be considered to include familial/genetic forms, virus-associated forms, drug-induced forms, and forms mediated by adaptive structural-functional responses (i.e., in the setting of congenital or acquired reduction of renal mass/nephron complement). Clinical response and prognosis may relate to the histologic variant, most notably the glucocorticioid responsiveness of the tip lesion and the aggressive, unrelenting nature of the collapsing variants (21,22). It is with this in mind that the variants are included in standard pathology reports.…”
Section: Classificationmentioning
confidence: 99%
“…In other studies the cellular lesion is more frequent in African Americans when nephrotic and nonnephrotic patients with FSGS are included, but in patients with nephrotic range proteinuria, the difference is no longer significant. When we consider the Columbia classification cellular variant is the least frequent, representing 3% of the case [6]. If the criteria of the Columbia classification are applied to a pediatric population with a high prevalence of African Americans, the ratio between the different variants changes, increasing the percentage of cellular type (32%).…”
Section: Clinical Featuresmentioning
confidence: 99%